What Would Deleuze Say? Tanja Ostojić’s Performances and Post-identity Thinking: Што би рекол Делез? Изведбите на Тања Остојиќ и постидентитетската мисла - Videkanić, Bojana; Janeva, Kalina (Identities: Journal for Politics, Gender and Culture, 2008)
Author(s): Bojana Videkanić | Бојана Видеканиќ Title (English): What Would Deleuze Say? Tanja Ostojić’s Performances and Post-identity Thinking Title (Macedonian): Што би рекол Делез? Изведбите на Тања Остојиќ и постидентитетската мисла Translated by (English to Macedonian): Kalina Janeva | Калина Јанева Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 7, No. 1-2 (Summer 2008 - Winter 2009) Publisher: Research Center in Gender Studies - Skopje and Euro-Balkan Institute Page Range: 117-141 Page Count: 24 Citation (English): Bojana Videkanić, “What Would Deleuze Say? Tanja Ostojić’s Performances and Post-identity Thinking,” Identities: Journal for Politics, Gender and Culture, Vol. 7, No. 1-2 (Summer 2008 - Winter 2009): 117-141. Citation (Macedonian): Бојана Видеканиќ, „Што би рекол Делез? Изведбите на Тања Остојиќ и постидентитетската мисла“, превод од англиски Калина Јанева, Идентитети: списание за политика, род и култура, т. 7, бр. 1-2 (лето 2008 - зима 2009): 117-141.